Corticoides intratimpánicos en el manejo de hipoacusia sensorioneural súbita - Rojas O., Mónica; Nazar S., Rodolfo (Revista Hospital Clínico Universidad de Chile, 2011)
Sudden sensorineural hearing loss (SSNHL) is defined as the loss of at least 30 dB in 3 or more consecutive frequencies in less than 3 days. It’s more frequent in the fifth decade, without gender-related differences. Although It is usually unilateral, 3% of patients may have both ears involved. 1% of cases are due to a retrocochlear disease. It presents as a rapidly progressive and sudden-onset hearing loss or that appears upon awakening. Over 90% of patients report tinnitus and 20 to 60% dizziness. Although many theories try to explain its origin, in only 20% of cases the etiology can be identified. The myriad of options have only reflected the lack of strong evidence on therapeutic alternatives and the high rate of spontaneous remission. Systemic corticosteroids in high doses have been defined as the standard therapy for SSNHL. Intratympanic steroid therapy has become a new alternative, allowing drugs to reach higher concentrations in the inner ear without the secondary effects of systemic therapy. Positive outcome has only been achieved using intratympanic steroids as salvage therapy. Authors disagree on its effectiveness, patterns of administration and posology. This paper reviews intratympanic steroid therapy, its advantages and disadvantages, its administration technique and its pharmacologic features.